The diplomatic making of EU-China relations: structure, substance and style - Xia, Q (2020)
The existing scholarly literature on EU-China relations is characterised by a dichotomous distinction between material and ideational factors and overemphasises the ‘interest versus values’ motif undergirding EU-China relations. The enigma of EU-China diplomatic relationship-building is compounded with a ‘relational gap’ in diplomatic studies. There is a dearth of a systemic theoretical framework that integrates the various dimensions of diplomatic relationship-building to interpret the dynamics of the process of diplomatic relationship-building. This study advances a novel theoretical model of diplomatic relationship-building and an associated social-network based research methodology to explore the making of EU-China relations through two in-depth case studies: the negotiations of the EU-China landmark agreement – the Agreement on Cooperation on, and Protection of, Geographical Indications (2009-2019) and the flagship EU-China climate-related bilateral cooperation – the EU-China Emission Trading System Project (2010-2019). The study purports that the making of EU-China relations is a process influenced by three essential elements – structural coordination, negotiations of technical and political substance, and the dialogue between the EU’s ‘walk the talk’ diplomatic style and China’s ‘shoulder responsibility’ diplomatic style. The process of EU-China diplomatic relationship-building is shaped by the fundamental underpinning of the relationship, encapsulated in EU-China shared intentions, which endow the EU and China with a ‘we-feeling’ that invokes shared vision and conveys the potential to unite the two parties. In so doing, the work provides a new theoretical arsenal to understand EU-China relations in a way that captures not only the ‘relational’ nature of diplomatic relationship-building but also takes us beyond the binary understanding of interests and values as sole motives in fostering international diplomacy, by integrating the social layer of ‘intentions’ in understanding diplomatic relationship-building. This work transcends traditional research in International Relations and has broader implications for exploring means by which the EU-China relationship can be better evaluated, managed and enhanced.